Lithostratigraphy of Nepalese Siwaliks: an appraisal for standardisation (Journal of Nepal Geological Society, 1998)
The Siwalik succession of Nepal is well studied indifferent sections of the entire country. The lithological successions of individual sections are very similar and comparable to each other. An attempt has been made to work out a unified lithostratigraphic classification of the Siwaliks for the entire country. Based on the available material, nine basic lithostratigraphic units has been proposed in ascending order; Bhorlegaon, Bankas, Jangli Khola, Chor Khola, Surai Khola, Dobata, Dudhaura, Ohan Khola and Deorali.Present study revealed the presence of a complete fossiliferous succession of the Nepalese Siwaliks along the Mahendra Highway from Surai Naka to Kalakate in western Nepal. Out of nine proposed units, eight are present in this section and hence, has been recommended as reference section for the study of the Siwalik sequence of Nepal.